Münster match
Una pequeña ampliación de una casa con atrio alemana construida en los años 60.
Keywords: BOLLES + WILSON; BOLLES, JULIA; WILSON, PETER; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; DISEÑO DE INTERIORES; ALEMANIA; MÜNSTER; AMPLIACION